2020
DOI: 10.3390/coatings10111069
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrical Properties and Stability of P-Type Conduction in ZnO Transparent Semiconductor Thin Films by Co-Doping Ga and N

Abstract: P-type ZnO transparent semiconductor thin films were prepared on glass substrates by the sol-gel spin-coating process with N doping and Ga–N co-doping. Comparative studies of the microstructural features, optical properties, and electrical characteristics of ZnO, N-doped ZnO (ZnO:N), and Ga–N co-doped ZnO (ZnO:Ga–N) thin films are reported in this paper. Each as-coated sol-gel film was preheated at 300 °C for 10 min in air and then annealed at 500 °C for 1 h in oxygen ambient. X-ray diffraction (XRD) examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…It was found that for the as-deposited ZnO:N films, the bandgap energy value was 3.25 ± 0.025 eV, while for the 400 °C and 550 °C RTA samples there was a slight reduction toward 3.20 ± 0.025 eV. These optical bandgap energy values are in good agreement with the literature reports [ 17 , 19 , 27 , 28 ]…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…It was found that for the as-deposited ZnO:N films, the bandgap energy value was 3.25 ± 0.025 eV, while for the 400 °C and 550 °C RTA samples there was a slight reduction toward 3.20 ± 0.025 eV. These optical bandgap energy values are in good agreement with the literature reports [ 17 , 19 , 27 , 28 ]…”
Section: Methodssupporting
confidence: 90%
“…However, to prepare a stable p-type ZnO film by N doping is rather difficult due to the low solubility of nitrogen, and thus the low concentration of holes in the films. Another obstacle to effective p-type doping via the replacement of O by N in the anion sublattice is the simultaneous generation of shallow and deep donor-type defects in the ZnO energy gap, such as oxygen vacancies in the O sublattice, V O , and zinc interstitials, Zn i [ 17 , 18 , 19 ], which leads to self-compensation of N acceptors in ZnO [ 20 ]. Difficulties in the preparation of p-type ZnO films have provoked interest in the studies of ZnO heterojunctions, mainly ZnO–Si heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, attention is now focused on obtaining and studying the properties of the ptype zinc oxide. Obtaining the p-type conductivity is complicated by the presence of natural oxygen vacancies, which act as donor states [4]. Today the following elements are acceptors for ZnO: Zn vacancies; IA group: Li, Na, K; IB group: Cu, Ag, Au; VA group: N, P, As, Sb [5].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different shaped nanostructures, such as nanorods, nanotubes, nanoneedles, nanowires, nanoflowers, nanospheres [27], plates [28], tetrapods [29], among others, can be deposited in different types of substrates to obtain ZnO films and layered junctions. Many deposition techniques can be used to develop ZnO thin films, including pulsed laser deposition [30], spray pyrolysis [7,31], sol-gel [32,33], RF sputtering [34] and chemical vapor deposition [35]. Among the deposition techniques, the sol-gel process stands out as a bottom-up approach for the production of electronic devices due to its controllable reaction conditions and low process temperatures, that allows the incorporation of organic and inorganic materials [36].…”
Section: Introductionmentioning
confidence: 99%